Meningkat Hasil Belajar IPA Melalui Model Pembelajaran Langsung - Hawa S Toluhula (Peneliti.net, 2022)
The purpose of this study was to obtain the results of the analysis and description of the application of the Direct Learning Model to improve student learning outcomes in learning the structure and function of plant parts. The research method is Classroom Action Research. The research subjects are students of SMA Negeri 1 Halmahera Utara, in class X with 19 students consisting of 9 male students and 10 female students. The results of the first cycle research that the average value of classical completeness only reached 71.05%. While the average value obtained by students in the second cycle increased to 85.78%. The conclusion is that the application of the Direct Learning Model can improve student learning outcomes. Suggestions to teachers and principals are expected to be able to apply the Direct Learning Model in science learning activities to improve student learning outcomes.